The 2021 ultrafast spectroscopic probes of condensed matter roadmap. (5th July 2021) - Lloyd-Hughes, J; Oppeneer, P M; Pereira dos Santos, T; Schleife, A; Meng, S; Sentef, M A; Ruggenthaler, M; Rubio, A; Radu, I; Murnane, M; Shi, X; Kapteyn, H; et al.
Abstract: In the 60 years since the invention of the laser, the scientific community has developed numerous fields of research based on these bright, coherent light sources, including the areas of imaging, spectroscopy, materials processing and communications. Ultrafast spectroscopy and imaging techniques are at the forefront of research into the light–matter interaction at the shortest times accessible to experiments, ranging from a few attoseconds to nanoseconds. Light pulses provide a crucial probe of the dynamical motion of charges, spins, and atoms on picosecond, femtosecond, and down to attosecond timescales, none of which are accessible even with the fastest electronic devices. Furthermore, strong light pulses can drive materials into unusual phases, with exotic properties. In this roadmap we describe the current state-of-the-art in experimental and theoretical studies of condensed matter using ultrafast probes. In each contribution, the authors also use their extensive knowledge to highlight challenges and predict future trends.